Carrier Transport and Photoresponse in GeSe/MoS2 Heterojunction p–n Diodes. Issue 22 (26th April 2018) - Tan, Dezhi; Wang, Xiaofan; Zhang, Wenjin; Lim, Hong En; Shinokita, Keisuke; Miyauchi, Yuhei; Maruyama, Mina; Okada, Susumu; Matsuda, Kazunari
Abstract: Simple stacking of thin van der Waals 2D materials with different physical properties enables one to create heterojunctions (HJs) with novel functionalities and new potential applications. Here, a 2D material p–n HJ of GeSe/MoS2 is fabricated and its vertical and horizontal carrier transport and photoresponse properties are studied. Substantial rectification with a very high contrast (>10 4 ) through the potential barrier in the vertical‐direction tunneling of HJs is observed. The negative differential transconductance with high peak‐to‐valley ratio (>10 5 ) due to the series resistance change of GeSe, MoS2, and HJs at different gate voltages is observed. Moreover, strong and broad‐band photoresponse via the photoconductive effect are also demonstrated. The explored multifunctional properties of the GeSe/MoS2 HJs are expected to be important for understanding the carrier transport and photoresponse of 2D‐material HJs for achieving their use in various new applications in the electronics and optoelectronics fields. Abstract : A 2D material p–n heterojunction of GeSe/MoS2 is fabricated and its vertical and horizontal carrier transport and photoresponse properties are studied. Substantial rectification behavior through the potential barrier in the vertical‐direction tunneling is observed. The negative differential transconductance with high peak‐to‐valley ratio (>10 5 ) is reported. Strong and broad‐band photoresponse via the photoconductive effect are demonstrated.